What traders know: the (mis)perceptions of formal and informal cross-border traders - Paolo Falco; Eleanor Wiseman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Cross-border traders face a choice between official and unofficial border crossings. The latter allow them to evade taxes, but expose them to other risks, such as bribes, fines, and arrest. We investigate the perceptions of cross-border traders about the risks of trading officially vs unofficially at the border between Kenya and Uganda. We find that traders overestimate the risks of trading officially relative to the same risks when trading unofficially. In reality, the measured risks of trading through the official border are lower.
Keywords: D73; F13; H26; Q17; 330; cross-border trade; formality; informality; beliefs; corruption